(PENGEMBANGAN BOOKLET HASIL EKSPLORASI TUMBUHAN BERPOTENSI ANTIHIPERTENSI DI SUKU ANAK DALAM DESA SUNGAI KIJANG) - Andriani, Silva (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2023)
AbstrackThis study aims to determine the types of antihypertensive plants, plant parts used as medicine, and how to process medicinal plants by the Orang Rimba community in Rawas Ulu District, Sungai Kijang Village, as well as find out the results of the development of the Antihypertensive Plant Exploration Booklet in the Suklu Anak Dalam tribe in Sungai Kijang Village, Rawas Ulu District. The results of the study found 12 species of plants from 10 families. The most widely used plant parts as medicine by the community are leaves (58.85%), while other plant parts used are fruit (30.77%), stems (7.69), rhizomes (7.69%). The most widely used method of processing medicinal plants by the suku anak dalam community in Sungai Kijang Village, Rawas Ulu District, is boiled (57.14%), grated (28.57%) and eaten lasungsung (14.29%). The results of the development of the booklet for the exploration of potentially antihypertensive plants in the suku anak dalam of Sungai Kijang Village, Rawas Ulu District, were carried out by three validators, namely material expert validators by 85%, media expert validators by 83%, linguist validators by 85%, and community readability questionnaires involving small groups of 10 people, showing that the booklet developed was feasible and did not need revision.